European Stroke Organisation (ESO) and European Association of Neurosurgical Societies (EANS) guideline on stroke due to spontaneous intracerebral haemorrhage - Steiner, Thorsten; Purrucker, Jan C.; Aguiar de Sousa, Diana; Apostolaki-Hansson, Trine ; 0000-0003-4063-5476; Beck, Jürgen; Christensen, Hanne; Cordonnier, Charlotte; Downer, Matthew B.; Eilertsen, Helle; Gartly, Rachael; Gerner, Stefan T.; Ho, Leonard; et al. (European Stroke Journal, 2025)
Spontaneous (non-traumatic) intracerebral haemorrhage (ICH) affects ~3.4 million people worldwide each year, causing ~2.8 million deaths. Many randomised controlled trials and high-quality observational studies have added to the evidence base for the management of people with ICH since the last European Stroke Organisation (ESO) guidelines for the management of spontaneous ICH were published in 2014, so we updated the ESO guideline. This guideline update was guided by the European Stroke Organisation (ESO) standard operating procedures for guidelines and the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) framework, in collaboration with the European Association of Neurosurgical Societies (EANS). We identified 37 Population, Intervention, Comparator, Outcome (PICO) questions and prioritised clinical outcomes. We conducted systematic literature searches, tailored to each PICO, seeking randomised controlled trials (RCT) – or observational studies when RCTs were not appropriate, or not available – that investigated interventions to improve clinical outcomes. A group of co-authors allocated to each PICO screened titles, abstracts, and full texts and extracted data from included studies. A methodologist conducted study-level meta-analyses and created summaries of findings tables. The same group of co-authors graded the quality of evidence, and drafted recommendations that were reviewed, revised and approved by the entire group. When there was insufficient evidence to make a recommendation, each group of co-authors drafted an expert consensus statement, which was reviewed, revised and voted on by the entire group. The systematic literature search revealed 115,647 articles. We included 208 studies. We found strong evidence for treatment of people with ICH on organised stroke units, and secondary prevention of stroke with blood pressure lowering. We found weak evidence for scores for predicting macrovascular causes underlying ICH; acute blood pressure lowering; open surgery via craniotomy for supratentorial ICH; minimally invasive surgery for supratentorial ICH; decompressive surgery for deep supratentorial ICH; evacuation of cerebellar ICH > 15 mL; external ventricular drainage with intraventricular thrombolysis for intraventricular extension; minimally invasive surgical evacuation of intraventricular blood; intermittent pneumatic compression to prevent proximal deep vein thrombosis; antiplatelet therapy for a licensed indication for secondary prevention; and applying a care bundle. We found strong evidence against anti-inflammatory drug use outside of clinical trials. We found weak evidence against routine use of rFVIIa, platelet transfusions for antiplatelet-associated ICH, general policies that limit treatment within 24 h of ICH onset, temperature and glucose management as single measures (outside of care bundles), prophylactic anti-seizures medicines, and prophylactic use of temperature-lowering measures, prokinetic anti-emetics, and/or antibiotics. New evidence about the management of ICH has emerged since 2014, enabling this update of the ESO guideline to provide new recommendations and consensus statements. Although we made strong recommendations for and against a few interventions, we were only able to make weak recommendations for and against many others, or produce consensus statements where the evidence was insufficient to guide clinical decisions. Although progress has been made, many interventions still require definitive, high-quality evidence, underpinning the need for embedding clinical trials in routine clinical practice for ICH.
Publisher Copyright: © European Stroke Organisation 2025
Keywords: Guideline; intracerebral haemorrhage; stroke; systematic review